Fluorine-free propionate route for the chemical solution deposition of YBa2Cu3O7−x superconducting films. Issue 3 (April 2015) - Nasui, M.; Petrisor., T.; Mos, R.B.; Gabor, M.S.; Mesaros, A.; Goga, F.; Ciontea, L.; Petrisor, T.
Abstract: The environmentally friendly fluorine-free propionate chemical solution deposition route has been developed for the epitaxial growth of YBa2 Cu3 O7− x (YBCO) superconducting films. In the present work, metal acetates are used as reagents to prepare a YBCO fluorine-free precursor solution. In order to determine the thermal decomposition behavior, the precursor powder obtained by drying the precursor solution was investigated by thermogravimetric analysis coupled with mass spectrometry and differential thermal analyses. The precursor films were deposited on SrTiO3 single crystal substrates by spin coating and subjected to a single-step thermal treatment. Fourier Transformed Infrared spectroscopy was used to study the decomposition of the films. The films have been structurally and morphologically characterized by X-ray diffraction and atomic force microscopy, respectively, and the superconducting properties have been measured by SQUID. The film composition was investigated by Auger electron spectroscopy. The as-deposited YBCO films show a sharp texture and good superconducting transport properties with T c =90 K ( R =0) and J c =0.8 MA/cm 2, respectively.